Processo de trabalho do agente comunitário de saúde : nas entrelinhas da revisão - Domingues, Caroline Couto (2017)
In this thesis, we presents a review about as the literatures approach the theme: work process of the Community Health Workers. A Research and analysis of scientific publications referring to the years 2000 to 2015 focusing on the macro and micropoliticals dimensions was realized. In addition, we analyze the potentialities and challenges reveled in the implementation of the Community Health Workers work process identified in the integrative review. 7841 papers were consulted, including articles, M.Sc. theses and Ph.D. theses of which 51 were selected according to the criteria adopted. Among the aspects of the macro dimension, we find attributions of the Community Health Works; Labor bond; Process of productive restructuring; Remuneration, among others. Already in the micropolitical dimension: bond with the community; teamwork; Governance; Professional valuation, among others. Already in the micropolitical dimension: bond with the community; teamwork; Governance; Professional valuation, among others. Among the potentialities, we have elaborated some categories: strategic worker to change the current care model; Production of a care-giver; Link between team and community; social role; Prevention and promotion actions; Intersectoral action; leadership; Knowledge of the territory; Strategies. We find that the Community Health Worker is a "sui generis" worker, with a community identity and who performs activities that go beyond the health field. In addition, a worker contributes to the concretization of what public health policy proposes. Among the challenges, we find lack of a clear definition of attributions; Precarious professional qualification; Social and environmental risks at work; Precariousness of work; work overload; Sub utilization; Low remuneration, among others. We find that faced with these challenges, the Community Health Worker experiences feelings of powerlessness, weariness, demotivation and psychic suffering. Thus, it is necessary the structuring of strategies that allow greater empowerment and autonomy to this professional, as is the proposal of Permanent Education, in order to discuss the macro and micropolitical aspects of daily life.